Development and Validation of a Smartphone-Based App for the Longitudinal Assessment of Anxiety in Daily Life. (June 2023) - Fortea, Lydia; Tortella-Feliu, Miquel; Juaneda-Seguí, Asier; De la Peña-Arteaga, Víctor; Chavarría-Elizondo, Pamela; Prat-Torres, Laia; Soriano-Mas, Carles; Lane, Sean P.; Radua, Joaquim; Fullana, Miquel A.
Current methods to assess human anxiety often ignore that anxiety is a dynamic process and have limitations such as high recall bias and low generalizability to real life. Smartphone apps using ecological momentary assessment (EMA) may overcome such limitations. We developed a smartphone app for the longitudinal evaluation of anxiety symptoms using EMA. We assessed the feasibility (retention and compliance) and psychometric properties (reliability and validity) of the app over 6 months in a sample of 99 participants with different levels of anxiety. The EMA-based smartphone app was highly feasible. It showed excellent within-person and between-person reliability, high convergent and moderate discriminant validity, and significant incremental validity. Assessing anxiety longitudinally using a smartphone and following EMA principles is feasible and can be reliable and valid. Studies combining EMA-based anxiety longitudinal assessments with other assessment methods deserve further research and may offer novel insights into human anxiety.